EVALUASI PROGRAM BIMBINGAN DAN KONSELINGDI SMKN 41 JAKARTA - Salman Tumanggor; Lulu Aufatuts Tsani (Hijri, 2019)
This study aims to evaluate the guidance and counseling program at SMKN 41Jakarta as supporting students in solving problem and developing students selfpotential. The evaluation model used is CIPP (Context, Input, Process, Product) toget a more comprehensive anin-depth picture of the guidance and counselingprogram.This study uses a qualitative approach wth descriptive methods. Data wasobtained from counseling and guidance coordinator, counselor, and students of SMKN 41 Jakarta using interview techniques, document studies, andobservations.The results of this study indicate that on the Context aspects, basedon the results of the achievement analysis are in the high category, as well as theinput aspects of the program which are also in the high category. The processaspect are in the high category, but in the product aspect it can be said to be in themoderate category. This the guidance and counseling program can be said to bewell organized, but in the category of moderate product still need to be improved. .In order to improve the implementation of the program, there are severalrecommendations that can be conveyed, there are:1) preparation of specialdocuments on the profile of guidance and counseling program; 2) preparation ofspecial document detail of funding for guidance and counseling program; and 3)addition of counseling and guidance counselor personnel.